The Relationship between Tutoring and Parenting Patterns with Primary School Students' Learning Achievement - Nur Safira Dyah; Ujang Efendi; Erni Mustakim (9 772338317006)
Abstract: The Relationship between Tutoring and Parenting Patterns with Primary School Students' Learning Achievement. The problems in this study are incorrect tutoring and parenting patterns and the learning achievements of learners who have not yet reached minimum criteria. The purpose of this study is to know the relationships of learning guidance and upbringing from parents with achievement of learning. This method of research is a correlational with a quantitative type. The population in this study is a class III protege with 110 elementary school learners, with 52 sample. Sample technique using a proporsional random sampling. Data collection using an angket, and a documentary. Research suggests that there is a link between study guidance and learning achievement and that there is a correlation between parent upbringing and learning achievement. As for a double-correlation study, there is a correlation between tutoring and parent upbringing and learning achievement.Keyword: tutoring, parenting, learning achievement.DOI : 10.23960/jmmp .v8.i3.2020